A critical role for suppressor of cytokine signalling 3 in promoting M1 macrophage activation and function in vitro and in vivo. Issue 1 (January 2014) - Arnold, Christina E.; Whyte, Claire S.; Gordon, Peter; Barker, Robert N.; Rees, Andrew J.; Wilson, Heather M.
Summary Macrophages respond to their microenvironment and develop polarized functions critical for orchestrating appropriate inflammatory responses. Classical (M1) activation eliminates pathogens while alternative (M2) activation promotes regulation and repair. M1 macrophage activation is strongly associated with suppressor of cytokine signalling 3 (SOCS3) expression in vitro, but the functional consequences of this are unclear and the role of SOCS3 in M1‐macrophage polarization in vivo remains controversial. To address these questions, we defined the characteristics and function of SOCS3‐expressing macrophages in vivo and identified potential mechanisms of SOCS3 action. Macrophages infiltrating inflamed glomeruli in a model of acute nephritis show significant up‐regulation of SOCS3 that co‐localizes with the M1‐activation marker, inducible nitric oxide synthase. Numbers of SOCS3hi‐expressing, but not SOCS1hi‐expressing, macrophages correlate strongly with the severity of renal injury, supporting their inflammatory role in vivo. Adoptive transfer of SOCS3‐short interfering RNA‐silenced macrophages into a peritonitis model demonstrated the importance of SOCS3 in driving production of pro‐inflammatory IL‐6 and nitric oxide, while curtailing expression of anti‐inflammatory IL‐10 and SOCS1. SOCS3‐induced pro‐inflammatory effects were due, at least in part, to its role in controlling activation and nuclear accumulation of nuclear factor‐κB and activity of phosphatidylinositol 3‐kinase. We show for the first time that SOCS3 also directs the functions of human monocyte‐derived macrophages, including efficient M1‐induced cytokine production (IL‐1β, IL‐6, IL‐23, IL‐12), attenuated signal transducer and activator of transcription 3 activity and ability of antigen‐loaded macrophages to drive T‐cell responses. Hence, M1‐associated SOCS3 was a positive regulator of pro‐inflammatory responses in our rodent models and up‐regulated SOCS3 is essential for effective M1‐macrophage activation and function in human macrophages.